Filip Melanchton i 500 lat jego Loci communes (1521) - Leszczyński, Rafał Marcin (Biuletyn Historii Wychowania, 2023)
In Poland, the Protestant Reformation of the 16th century is most often associated with Martin Luther. However, together with Luther, the reforms were introduced into the Church by Ulrich Zwingli in Zurich, while Philip Melanchthon, Luther’s friend and collaborator, was a very important theologian in Germany. It was him who determined the ultimate doctrinal and organizational form of Lutheranism. Melanchthon was a theologian and a humanist, the reformer of German education, author of numerous textbooks widely used in all over Renaissance Europe, including Poland and Lithuania. One of Melanchthon’s major textbooks was Loci communes (1521). In this book, Melanchthon made an attempt to systematize evangelical doctrines. Consequently, it is considered the first evangelical theology textbook and, at the first time, the first work on Protestant dogmas.